The Department Chair Academy at the University of Houston-Downtown - Edmund Paul Cueva; Lucy Bowen (Academic Chairpersons Conference Proceedings, 2020)
Presenters and participants will discuss a chair academy model that has had successful results. The topics covered in this presentation include the fundamental components of the academy (format, curriculum, activities), the origin of and need for the academy, and the results of a survey on the efficacy of the academy.
Keywords: work-life; faculty; departmental culture; academic leadership; career flexibility